Continuous Integration/ Continuous Delivery Optimization on Network Automation using Gray Wolf Optimizer - Ronald Adrian; Anni Karimatul Fauziyyah; Sahirul Alam (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Continuous Integration/ Continuous Delivery is the latest method used in network automation. In-network programming has helped network admins a lot in managing all their devices. One of the real-time networks needs to force network admins to be able to provide data quickly. Deployment speed can be increased to provide up-to-date data or network configuration. To tackle these problems, we propose implementing the GWO algorithm in the Continuous Integration/Continuous Delivery process. This algorithm is proven to be superior in the speed of finding the value of the objective function compared to other similar algorithms. The results obtained indicate that the convergence time is faster by 74%. This value has an impact on increasing program deployment speed by 41.2%. These results indicate that the GWO algorithm can be an alternative to increasing the speed of Continuous Integration/ Continuous Delivery.